Tribological performances of journal bearing using palm oil based lubricant - Paiman, Zulhanafi (2021)
The green technology policy and strict environmental legislation have driven researchers to focus their attention to bio-based lubricants. Bio-based lubricants are known to have excellent biodegradability characteristics, but low oxidative stability and limited viscosity range. The purpose of this research was to analyze the tribological performances of journal bearing using palm oil-based lubricants. In this study, few types of palm oil-based lubricants went through a tribological test using a four-ball tribotester by following ASTM D4172B and D2783 standards accordingly. Results revealed that Palm Mid Olein (PMO) exhibited excellent performance in terms of friction coefficient and wear scar diameter (WSD) compared with other palm oil-based lubricants. The addition of 0.045 % tertiary-butyl hydroquinone (TBHQ) and 1.3 % ethylene vinyl acetate (EVA) resulted in a 4.5-fold increase in oxidative stability and 19.16 % increase in viscosity index, respectively. PMO+TBHQ+EVA also showed a 16.05 % decrease in friction coefficient and 8.89 % decrease in WSD compared with raw PMO. Furthermore, the performance of PMO+TBHQ+EVA was evaluated by using a journal bearing test rig and compared with that of raw PMO. Results revealed that PMO+TBHQ+EVA showed 72.1 % higher maximum oil film pressure, 47.5 % lower friction coefficient, and 51.2 % higher load carrying capacity when compared to PMO alone. In addition, it was observed that dimples with a spherical shape showed 6.8 % higher maximum oil film pressure, 21.5 % lower friction coefficient, 5.26 % higher load carrying capacity, and 39.6 % higher minimum oil film thickness than dimples with a conical shape. The combination of PMO+TBHQ+EVA co-acting with a spherical shape profile also resulted in optimum performance in journal bearing operation. It is suggested that the addition of TBHQ and EVA successfully improves the characteristics of base stock palm oil (PMO) and the combination of PMO+TBHQ+EVA with the spherical shape of dimple’s bottom profile offers comparable performance in journal bearing operation.